2003
DOI: 10.1177/107906320301500302
|View full text |Cite
|
Sign up to set email alerts
|

Distorted Attitudes and Perceptions, and Their Relationship With Self-Esteem and Coping in Child Molesters

Abstract: Two studies were conducted to compare various aspects of child molesters, non-sexual offenders, and community-based nonoffenders. These studies were aimed at examining some implications of our general model of sexual offending. Study 1 compared the responses of these 3 groups on measures of self-esteem, attitudes toward women and children, and social desirability tendencies. The only observed difference was that child molesters had significantly lower self-esteem than did the other 2 groups. In Study 2, child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 31 publications
2
35
0
2
Order By: Relevance
“…Sexual offenders were excluded because of the heterogeneity of self-esteem among sub-categorizations of such prisoners (e.g., Kalichman, 1991;Marshall, Marshall, Sachdev, & Kruger, 2003;Shine, McCloskey, & Newton, 2002). Paramilitary prisoners were excluded because they frequently report that they are not criminals, even to the extent that they do not associate with nonparamilitary prisoners and retain their rank structure within the prison (e.g., Jamieson & Grounds, 2002;Mitchell, 2003).…”
Section: Similar To Positive Similar To Negativementioning
confidence: 99%
“…Sexual offenders were excluded because of the heterogeneity of self-esteem among sub-categorizations of such prisoners (e.g., Kalichman, 1991;Marshall, Marshall, Sachdev, & Kruger, 2003;Shine, McCloskey, & Newton, 2002). Paramilitary prisoners were excluded because they frequently report that they are not criminals, even to the extent that they do not associate with nonparamilitary prisoners and retain their rank structure within the prison (e.g., Jamieson & Grounds, 2002;Mitchell, 2003).…”
Section: Similar To Positive Similar To Negativementioning
confidence: 99%
“…Schweighofer (1993) also detected a meaningful difference between sex offenders and non-offenders in terms of cognitive distortions regarding rape. Sex offenders have more cognitive distortions than non-offenders when considering rape as a crime (Hanson et al 1994, Marshall et al 2003, Stermac and Segal 1989. Cognitive distortions include reactions such as rationalization, accusation, denial, excuses, and the observed difference between sex offenders and non-offenders is not an unexpected result.…”
Section: X Xmentioning
confidence: 97%
“…Perpetrators' behaviors could be explained by the feelings of worthlessness and low self-esteem that previous studies indicated as an integral reasons for preference for children (Milner & Webster, 2005;Marshall, 2003). On the surface, young boys trusted and respected adult scoutmasters.…”
Section: Significances Of Analysesmentioning
confidence: 89%
“…In the meantime, offenders' behaviors were at the center of attention for analysis to determine their potential risk factors and effective offender treatment strategies (Abel et al, 1994). A primary reason for child molestation identified in the previous studies is some sense of personal vulnerability, such as social incompetence and low self-esteem (Gilgun, 1994;Marshall, Marshall, Sachdev, & Kruger, 2003;Milner & Webster, 2005;Marshall, Champagne, Brown, & Miller, 1997;Terry, 2013).…”
Section: Reasons For Child Molestationmentioning
confidence: 99%
See 1 more Smart Citation